Knowledge transfer within strategic alliances in the life science industry - Aziz Azrina (2008)
The study aims to explore the flow of knowledge in the life science industry, and to develop a framework for knowledge transfer involving alliances. We focused our attentionon the various mechanisms that may facilitate knowledge flows. In the process, we identified the enablers and processes that will enhance the effectiveness of knowledge transfer between different alliance designs.